Chaperone-mediated autophagy as a therapeutic target for Parkinson disease. (3rd October 2018) - Campbell, Philip; Morris, Huw; Schapira, Anthony
ABSTRACT: Introduction : Parkinson disease (PD) is the most common neurodegenerative movement disorder. Currently only symptomatic treatments exist for PD, and so the search for potential neuroprotective drug targets is of great importance. Chaperone mediated autophagy (CMA) is one of the key cellular mechanisms in protein homeostasis. Many of the pathogenic pathways thought to be important in PD converge on CMA, thus rendering it an attractive therapeutic target. Areas covered : In this review we discuss current up-to-date knowledge of the molecular mechanisms involved in CMA function and regulation. We go on to discuss the links between CMA and PD including CMA's role in ɑ-synuclein processing, oxidative stress, and mitochondrial function. We finish by exploring the potential benefits of how upregulation of CMA may be beneficial in PD and strategies to achieve this. Expert opinion : Upregulation of CMA is an attractive therapeutic target in PD due to its links with several pathogenic pathways . Currently more knowledge of the mechanisms that regulate CMA is required to allow for the development of specific CMA modulators. However, recent studies demonstrating the role of retinoic acid derivatives and miRNAs in regulating CMA are promising, and indirect upregulation of CMA by modulating other lysosomal pathways may be helpful.